Empirical Evaluation of Construction Material Waste Generated on Sites in Nigeria - Adewuyi, T.O.; Idoro, G.I.; Ikpo, I.J. (Institute of Research and Community Outreach - Petra Christian University, 2014)
The study investigates the level of construction material waste generated on building sites in South-South, Nigeria. The objective is to empirically establish the level of waste generated on building sites and compare such with the allowable value in estimates. Data were collected from 30 on-going public building projects for six months. The level of material waste was calculated in percentages while one way ANOVA was employed to compare the waste values among the States in the zone. The significant difference between actual and allowable values of waste was tested using paired t-test. The level of material waste was found to be 11.69, 12.10, 10.45, 14.54, and 12.07 for concrete blocks, steel reinforcement, timber, and tiles respectively. It was concluded that these values are significantly different, with p-values < 0.05, from the allowable waste. The study recommends that the values of waste derived by this study be adopted in estimates